Yasar, Kerim. 2018. Electrified Voices: How the Telephone, Phonograph, and Radio Shaped Modern Japan, 1868–1945. New York: Columbia University Press. - Cressy, Thomas A. (Current Musicology, 2018)
Kerim Yasar’s Electrified Voices is an innovative study on how sound technologies developed in Japan from 1868 to 1945. It includes detailed examples of how sound was central to the creation of a modern subjectivity and used by the Japanese nation state for ideological reasons. The volume is a valuable addition to scholarship on the relationships among sound, technology, modernity, and the nation state in Japan. After an introductory chapter, the main body of the argument is divided into six separate and chronologically ordered chapters—each dealing with aspects of sound and technology in Japan—and a short “coda” to finish. I discuss each chapter in turn below.